Chemical Profiling and Wetting Behaviors of Endemic Salvia absconditiflora Greuter & Burdet (Lamiaceae) Collected from Gypsum Areas - Ayşenur Kayabaş; Ertan Yıldırım (European Journal of Biology)
Objective: Salvia absconditiflora Greuter & Burdet is an endemic plant and survives in nature by adapting to extreme conditions. The aims of this study are to characterize and compare the diversity in the spectral-chemical structure of S. absconditiflora’s plant parts using the FTIR spectroscopy technique, to determine the wettability of the adaxial and abaxial epidermal surfaces of S. abscontidiflora leaves and to interpret whether there is a difference between the contact angle (CA) measurements at the points determined in the surface area of the leaves from the part close to the petiole to the leaf tip. Materials and Methods: The ATR-FTIR spectra for the chemical content of S. absconditiflora were obtained from six different plant parts and information about their chemical compositions was obtained. CA measurements were carried out for the natural events of the leaf area, especially for the water holding capacity or hydrophilic-hydrophobic characteristics.Results: The biochemical fingerprint of S. absconditiflora was determined by the analysis of chemical groups in vegetative and generative plant parts using ATR-FTIR spectroscopy. The CAs showed that the leaf had a hydrophobic character. In addition, leaf hysteresis was determined for each plant part, and it was understood that the lotus effect also appeared in S. absconditiflora. Conclusion: Detailed biochemical profiling, wettability, and hysteresis reports of S. absconditiflora were created for the first time. With this study, important clues about the adaptation of plants to harsh conditions were obtained.